2012
DOI: 10.1055/s-0032-1327653
|View full text |Cite
|
Sign up to set email alerts
|

Figure Skater Level Moderates Balance Training

Abstract: It was suggested that baseline levels of postural control in figure skaters might influence the effectiveness of neuromuscular training. The aims of the present study were to investigate the baseline association of skater skill level with standard center of pressure metrics and time to stabilization, and to determine if skill level influenced the effectiveness of a 6-week neuromuscular training program. There was no main effect of skill level for any baseline center of pressure metric for either test. There wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 6 publications
0
12
0
1
Order By: Relevance
“…However, a few articles stated that such effect did not occur (Eisen et al, 2010; Mahieu et al, 2006; Malliou et al, 2004; Sato and Mokha, 2009; Saunders et al, 2013; Verhagen et al, 2005), and a few studies, in which the effect was not reflected in all balance measures, suggested that balance training did not influence all of the dimensions of postural control (Benis et al, 2016; Holm et al, 2004; Pau et al, 2011; Zech et al, 2014). In some cases where the authors carried out both static and dynamic tests, significant results occurred in only one test type.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, a few articles stated that such effect did not occur (Eisen et al, 2010; Mahieu et al, 2006; Malliou et al, 2004; Sato and Mokha, 2009; Saunders et al, 2013; Verhagen et al, 2005), and a few studies, in which the effect was not reflected in all balance measures, suggested that balance training did not influence all of the dimensions of postural control (Benis et al, 2016; Holm et al, 2004; Pau et al, 2011; Zech et al, 2014). In some cases where the authors carried out both static and dynamic tests, significant results occurred in only one test type.…”
Section: Discussionmentioning
confidence: 99%
“…More sophisticated procedures were performed on a force plate (FP) which can monitor the movement of the center of pressure (COP). Different variables derived from the path of the COP during the single leg stance test (Ahmadabadi et al, 2015; Malliou et al, 2004; Saunders et al, 2013), the quiet standing (QS) test (Cankaya et al, 2015; Pau et al, 2011; Steib et al, 2016) or the limit of stability (LOS) test (Mahieu et al, 2006; Romero-Franco et al, 2012) have been used as measures of balance. A balance assessment can also be conducted on an unstable surface.…”
Section: Balance Trainingmentioning
confidence: 99%
See 1 more Smart Citation
“…(2) The signal processing (smoothing) of the input varied from no processing, i.e. using the 'raw' GRF signal (RAW) [3,5,16,22,23,[26][27][28][29], sequential averaging (SA), by adding one data point at a time, and calculating a new average after each added point [1,5,7,8,14,16,20,23,26,27,30], fitting an unbounded 'third order polynomial' (TOP) starting at the peak GRF, using the following function: f(x) = a 0 + a 1 x + a 2 x 2 + a 3 x 3 , where Third order polynomial Average range of variation (10-20 s window) + 3 SD a Signal to threshold [12,13,[17][18][19] An overview of the calculation methods identified, based on the processed signal, threshold and definition of TTS. a Threshold averaged over n trials.…”
Section: Identification Of Tts Calculation Methodsmentioning
confidence: 99%
“…A number of studies differentiated between participants, tasks or interventions using the TTS, examining the effect of chronic ankle instability (CAI) [7,14], functional ankle instability (FAI) [5,6,[9][10][11]13,15], anterior cruciate ligament (ACL) deficiency and/ or reconstruction [16,17], jumping distance [18], jumping direction [8], fatigue [1,3,19], ankle brace [1], injury prevention programme [4], neuromuscular training [20], stochastic resonance stimulation [21] and plyometric exercises [22]. Time to stabilization (TTS) is the time it takes for an individual to return to a baseline or stable state following a jump or hop landing.…”
Section: Introductionmentioning
confidence: 99%